Localization of rainfall and determination its intensity in the lower layers of the troposphere from the measurements of local RF transmitter characteristics - PODHORSKÝ, Dušan; FABO, Peter (Contributions to Geophysics and Geodesy, 2016)
The article deals with a method of acquiring the temporal and spatial distribution of local precipitation from measurement of performance characteristics of local sources of high frequency electromagnetic radiation in the 1–3GHz frequency range in the lower layers of the troposphere up to 100 m. The method was experimentally proven by monitoring the GSM G2 base stations of cell phone providers in the frequency range of 920–960MHz using methods of frequential and spatial diversity reception. Modification of the SART method for localization of precipitation was also proposed. The achieved results allow us to obtain the timeframe of the intensity of local precipitation in the observed area with a temporal resolution of 10 sec. A spatial accuracy of 100m in localization of precipitation is expected, after a network of receivers is built. The acquired data can be used as one of the inputs for meteorological forecasting models, in agriculture, hydrology as a supplementary method to ombrograph stations and measurements for the weather radar network, in transportation as part of a warning system and in many other areas.